TRANSMISI HARGA DAN SEQUENTIL BARGAINING GAME PERILAKU PASAR ANTAR LEMBAGA PEMASARAN CABE MERAH DI INDONESIA - Elvina Elvina; Muhammad Firdaus; Anna Fariyanti (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2017)
Red chili is known as a very high commodity price fluctuation. High price fluctuation will make market inefficiency and cause a disincentive for market actors. One indicator of market efficiency is symmetric price transmission in integrated market. This paper aimed to analyze vertical price transmission along the marketing chanel of red chili (produsen, wholesale and retail) and analyze the market behavior of market actors. Vertical price transmission was analyzed with the Asymmetric Error Corection Model (AECM) approach using weekly data over Januari 2012 to October 2014. While, the market behavior was analized using descriptive analysis with sequentil bargaining game. The results showed that price transmission along marketing channel of red chili is symmetric and the price in wholesale is a reference for produsen dan retail prices.